AKTIVITAS ANTIBAKTERI ACTINOMYCETES DARI AKAR TANAMAN DI EKOSISTEM KARST GORONTALO, INDONESIA - Alfandi Kibu; Yuliana Retnowati; Novri Youla Kandowangko; Wirnangsi Din Uno; Abubakar Sidik Katili; Nurdin (Pojok Publisher, 2025)
Several pathogenic bacteria such as Staphylococcus aureus, Escherichia, Pseudomonas aeruginosa and other pathogenic bacteria have developed resistance to many marketed antibiotics. Staphylococcus aureus is already resistant to several types of antibiotics such as penicillin, erythromycin, cefoxitin, levofloxacin, and clindamycin, Escherichia is resistant to several antibiotics such as Penicillin G, Cefotaxime, Tetracycline, Ampicillin, and Amoxicillin, Pseudomonas aeruginosa has been resistant to antibiotics that target ribosomes, such as tobramycin and tigecycline. The problem of resistance of several pathogenic bacteria can be overcome by finding new metabolite compounds from Actinomycetes microorganisms that have antibiotic potential by exploring extreme areas, one of which is in the karst area, especially in plant roots. Root sampling was carried out by taking samples + 20 cm on each type of plant found. Isolation of Actinomycetes bacteria was carried out using the plate method. Antibacterial activity testing was carried out using the line method. The morphological form of the spores was seen using a SEM (Scanning Electron Microscope). The results of the study found 2 isolates of isolated plant roots containing Actinomycetes bacteria. 2 isolates showed morphological characteristics of mycelium, oval and round in shape and had various colors. The results of the antibacterial activity test showed that each isolate could inhibit several types of pathogenic bacteria, seen from the clear zone with different diameters and the results of SEM (Scanning Electron Microscopy) showed that 2 isolates had the same character and shape of spores as Actinomycetes, namely the genus Streptomyces.